Bentuk Tari Anak Tengah Di Sanggar Seni Tuah Merindu Kecamatan Pulau Beringin Kabupaten Oku Selatan - Rani Rahma Dewi; Hasan; Efita Elvandari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to find out and describe the dance forms of middle children in the Tuah Merindu art studio, PulauBeringin District, South OKU Regency. The method used in this research is a qualitative descriptive method discussing the dance forms of middle children. This research uses primary data sources and secondary data sources. The data collection techniques used are observation techniques, interview techniques and documentation techniques. The results of this research, the middle child dance was created in 2019 which has the meaning